L’expérience difficile du travail enseignant et les besoins de soutien chez les enseignants débutants au Québec - Joséphine Mukamurera; Sawsen Lakhal; Maurice Tardif (Activités)
Our research aims, on the one hand, to highlight teaching work as experienced by novice teachers on a daily basis and, on the other hand, to identify the nature of perceived support needs during their first years of teaching. Our theoretical framework is based on a global and multidimensional approach to professional integration and teaching work. The study includes a qualitative component based on 32 semi-structured interviews and a quantitative component based on a secondary analysis of data survey (250 respondents). The qualitative results revealed task diversity and heaviness, as well as differences between recognized workloads and actual teaching loads, as experienced on a daily basis. In addition, the quantitative results confirmed the multidimensional nature of support needs in five areas : organizational socialization, classroom management, learning management, educational differentiation and personal and psychological aspects. Comparative analyses using ANOVA tests showed some differences between the groups of teachers on their perception of support needs, in terms of teaching orders, fields of teaching and fields of training. These results bring new insights into teaching work and offer avenues to guide support offers to beginning teachers and the design of teacher programs.